Detection Hand Motion on Virtual Reality Mathematics Game with Accelerometer and Flex Sensors - Erdhi Widyarto Nugroho; T. Brenda Chandrawati (Universitas Ahmad Dahlan, 2018)
Montessori method is a learning method using props. One of the developments props is to use the game as a medium of learning. The examples Game media as learning is the use of Virtual Reality or VR Technology. By using the VR, players will be brought into the virtual world as if the player is in the real world. The weakness of the VR game is the limited interaction with the outside world. Interaction uses only buttons and joysticks. In this paper we use Flex sensor and accelerometer sensor to detect hand movements for VR mathematic game. The result is VR games are more interactive and interesting with hand motion.